Pencegahan dan Tatalaksana Stroke di Wilayah Puskesmas Maccini Sawah - Abd. Herman Syah Thalib; Ricky. Z; Rusli Abdullah; Nur Aliza Aszahra; Ainun Ainun (Universitas Muhammadiyah Manado, 2020)
Stroke is a non-communicable disease that still has the highest death rate in the world. Even though stroke is not transmitted from one sufferer to another through contact, prevention must still be improved. Lifestyle and socioeconomics are thought to be one of the biggest factors that cause strokes. This activity aims to prevent and manage stroke by increasing knowledge in detecting signs and symptoms of stroke, preventing recurrent strokes and changing lifestyle modification behavior. Community service activity methods include health education, health checks to identify risk factors for hypertension/stroke, empowering families to recognize signs and symptoms of stroke, controlling stroke risk factors and lifestyle modification. The results of the activity showed that the majority of respondents had had one stroke (60%), the majority of families had sufficient knowledge (60%) about preventing recurrent strokes, the majority of respondents had a low risk (50%). Increased knowledge of patients and families in detecting signs of preventing stroke risk factors is targeted at changing behavior and improving healthy lifestyles to prevent recurrent strokes.